Материалы к фауне и экологии трубковертов (Coleoptera, Attelabidae) Украины. Сообщение II - Лаврух, О.В. (Вестник зоологии, 1972)
Materials are presented on faunistic composition, ecological peculiarities, distribution and economic significance of seven species of Attelabidae from the genera Вуctiscus T h o m s., Chonostropheus P r e l l., Deporaus S a m., Attelabus L., Apoderus О l. Besides, the corresponding generalized data on 29 species of Attelabidae are given as well as information on their habitat and zoogeographical distribution.